Construction of targeted and integrative promoter-reporter plasmids pDK-K and pDK-G to measure gene expression activity in Haemophilus parasuis. (September 2019) - Dai, Ke; Yang, Zhen; Chang, Yung-Fu; He, Lvqin; Cao, Sanjie; Zhao, Qin; Huang, Xiaobo; Wu, Rui; Huang, Yong; Yan, Qigui; Han, Xinfeng; Ma, Xiaoping; et al.
Abstract: Haemophilus parasuis ( H. parasuis ) is rather difficult to manipulate genetically due to the diversity of restriction-modification systems and other mechanisms harbored by various isolates. This prevents exogenous plasmids from replicating in this species and hinders research efforts focused on transcriptional regulators in this bacterium. In this study, we generated a convenient promoter reporter system based on gene knock-in method using natural transformation in H. parasuis . Gene knock-in has proven useful as a powerful tool facilitating identification and studying the transcription activities of regulators under a variety of conditions that favor gene transcription or expression from an incorporated promoter. The vectors, pDK-K and pDK-G, carrying promoterless reporter lacZ gene and two homologous sequences flanking a knock-in site, may have some advantages over the extensively used plasmid-bearing reporter system in other bacteria in stability and ease of genetic manipulation in H. parasuis . The knock-in site was positioned at a site occupied by flanking genes that were both hypothetical and had the same transcription orientation, thus the expression of the reversely cloned promoter- lacZ fusion wouldn't be affected by the upstream promoter on the chromosome. The expression activity of lacZ gene under the transcriptional activation of a 300 bp promoter-proximal segment of cyaA, crp or comA genes in H. parasuis was separately validated using X-gal and o -nitrophenyl-β-d -galactoside(ONPG) as substrates. The derivatives harboring promoter- lacZ fusion segments showed significantly higher β-galactosidase activity levels than the promoterlessones both in TSB++ broth and on TSA++ plate as screened either by X-gal method or the standard Miller method. We also used pDK vector to further certify that the cyaA promoter is inducible and whose transcriptional levels were in correlation with the growth kinetics of the bacteria in TSB++. With this system, gene knock-in method based on natural transformation in H. parasuis proved to be useful in identifying transcriptional regulation of a certain promoter. Highlights: The plasmid consists of Kan/Gm antibiotic cassette, promoterless reporter lacZ gene and two homologous sequences flanking a knock-in site in H. parasuis, as well as the E. coli ori site colE1 . The plasmids pDK-K/G are suicide vectors that can efficiently knock-in the promoter- lacZ -Kan/Gm fusion into a certain site of H. parasuis strain SC1401 and EP3, which were chosen as the recipient strains for their defect in utilizing lactose and the characteristic of natural competence. The pDK promoter reporter system could efficiently (both qualitatively and quantitatively) verify the transcriptional activity of the cloned promoter, without any polarity effect.